WOMEN EMPOWERING THROUGH DECOUPAGE - Hommy Dorthy Ellyany Sinaga; Petrus Loo; Dedy Lazuardi; Sri Rezeki; Norhaslina BT Asri; Mashitah Binti Duralim; Nur Fadzillah Binti Jaafar (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2024)
Abstract: The community service activity "Women Empowering Through Decoupage," conducted in continuation of the Memorandum of Understanding with Sultan Azlan Shah Malaysia Polytechnic, was organized by several lecturers at Sekolah Tinggi Ilmu Ekonomi Eka Prasetya from October 2nd to October 5th, 2023. The target participants were Puspanita (Wives of Lecturers/Employees) of Sultan Azlan Shah Malaysia Polytechnic. The activity focused on training participants in decorating pandan clutch using decoupage techniques. This collaboration between lecturers at Eka Prasetya College of Economics and Sultan Azlan Shah Malaysia Polytechnic lecturers aimed to empower Puspanita by imparting new knowledge and skills. The production outcomes potentially hold economic value. The activity garnered a highly positive response from all participants.            Keywords: decoupage; pandan clutch; puspanita; sultan azlan shah malaysia polytechnic; women empowering,  Abstrak: Kegiatan Pengabdian Kepada Masyarakat Women Empowering Through Decoupage dilakukan sehubungan dengan kelanjutan dari MoU dengan Politeknik Sultan Azlan Shah Malaysia. Kegiatan ini dilaksanakan oleh beberapa Dosen Sekolah Tinggi Ilmu Ekonomi Eka Prasetya dan berlangsung pada 2-5 Oktober 2023, dengan sasaran peserta adalah Puspanita (Istri dari Dosen/Pegawai) Politeknik Sultan Azlan Shah Malaysia. Aktivitas yang dilakukan adalah dengan memberikan pelatihan pembuatan menghias tas pandan dengan menggunakan Teknik decoupage. Pengabdian kepada Masyarakat ini merupakan kolaborasi dosen Sekolah Tinggi Ilmu Ekonomi Eka Prasetya dengan dukungan Dosen dari Politeknik Sultan Azlan Shah Malaysia. Dari kegiatan ini, para Puspanita mendapatkan pengetahuan dan ketrampilan yang baru. Hasil produksi dapat menjadi peluang bernilai ekonomis. Kegiatan ini mendapat respon yang sangat positif dari seluruh peserta. Kata kunci: decoupage; cluth pandan; pemberdayaan perempuan; politeknik sultan azlan shah; puspanita